INTRODUCTIONS AND THEIR IMPORTANCE IN SPEECH, DIFFERENCES FROM INDEPENDENT WORDS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article discusses in detail the artistic features of the inserts, their importance in speech. Its differences from independent word groups are illustrated by examples